The Rise of Digital Money : A Strategic Plan to Continue Delivering On The IMF's Mandate. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2021)
Rapid technological innovation is ushering in a new era of public and private digital money, bringing about major benefits in terms of efficiency and inclusion. To reap the full benefits and manage risks, authorities around the world will have to address new policy challenges. These are widespread, complex, rapidly evolving, and have profound implications. This paper identifies the main challenges currently arising regarding consumer protection and financial integrity, domestic financial and economic stability, as well as the stability and efficiency of the international monetary system. The paper argues that many of these challenges intersect the Fund's mandate. The Fund must therefore monitor, and advise on, this rapid and complex transition for all members. The paper ends with a broad vision of how to deliver on this mandate and serve its members, including by enhancing resources, and collaborating closely with other institutions. This is the first of two papers, the second of which lays out a more detailed operational strategy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Monetary Policy; Monetary Systems; Political Economy; Regimes; Standards